Communication Skill in Medical Practice - Sharma, Anup (Journal of Nepalgunj Medical College, 2024)
Communication is a process by which we relate and interact with people. It’s a mutual process between two sides and includes listening and understanding with passion and respect. Communication is an art and like other arts it is a learned skill. Effective communication is the basis of mutual understanding and trust, which is very important in Medicine. Traditionally, in Medical Training, emphasis was given to the knowledge and Medical proficiency than to the communication skill. Today patient’s perception of a good doctor is based on good verbal and non-verbal skills, approachable personal attributes and finally knowledge of their subjects. So learning communication skill and evidence based practice become the corner stones of modern Medicine. Doctors need to learn essentials of good communications than other professionals because patients are humans with emotions and sensitive needs. Doctors cannot practice Medicine without effective communication skills and poor communication causes a lot of complaints, dissatisfaction and medico legal problems. Effective communication skill ensures good working relationship, increases patients satisfaction, improves patient compliance with treatment and is a key to success in professional career. In the recent years we have been observing increasing numbers of litigation against doctors, vandalism in the hospitals. One of the leading factors in happening of such things is a poor communication with the patient and his relatives. The reason behind this lacking of communication skill in doctors is we have never been taught this subject during our training. Soft skill courses such as Health Care Management, Medical Ethics and Professionalism, communication skills are not included neither in the MBBS nor in Master Level Curriculum so far. Hence it is a strong recommendation to the Medical Education Regulatory bodies of our country to incorporate such soft skills in the MBBS Curriculum as a compulsory subjects and also to have some sort of assessments of these skills during the course.